Penguasaan Tanah Ulayat yang Belum Terdaftar oleh Investor melalui Kontrak Karya: Tinjauan Yuridis terhadap Kasus PT Gag Nikel - Dewanata, Bhisma; Ridaningjati, Pamungkas; Tobing, Daniel Giovanni Pandapotan L.; Farisi, Gusti Muhammad Reyhan; Alamsyah, Ariij Salsabil; Fatoni, Rifky Hamdan; Hutami, Aisya Puteri; Danu, Nizar Naren; Qatrunnada, Amirah (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
The acquisition of customary land by mining companies often raises legal issues. Although customary land has constitutional recognition, the lack of administrative registration creates legal uncertainty, especially when ethics align with significant interests such as investment. This article analyzes the legality of PT Gag Nikel's acquisition of customary land, which operates under a Contract of Work (CoW), within the context of Law Number 4 of 2009 concerning Mineral and Coal Mining, as amended by Law Number 3 of 2020 (hereinafter referred to as the Minerba Law). This research uses legal research methods with statutory, conceptual, and case-based approaches. The results indicate that agreements between companies and indigenous communities are valid only if they meet consensual requirements and do not conflict with higher-level laws. Unauthorized agreements have low binding force and are vulnerable to revocation, especially when there is resistance from the aggrieved party or indications of default, as in the case of PT Gag Nikel. This article offers recommendations for legal reconstruction regarding the formal legalization mechanism for customary land agreements to strengthen the protection of indigenous communities while providing certainty for investors.